Comparing reappraisal and acceptance strategies to understand the neural architecture of emotion regulation: a meta-analytic approach - Monachesi, Bianca; Grecucci, Alessandro; Ahmadi Ghomroudi, Parisa; Messina, Irene (Frontiers in Psychology, 2023)
In the emotion regulation literature, the number of neuroimaging studies on cognitive reappraisal has created the impression that the same top-down, control-related neural mechanisms characterize all emotion regulation strategies. However, it is possible that top-down processes coexist with more bottom-up and emotion-focused processes that partially bypass the recruitment of executive functions. A case in point is acceptance-based strategies. To better understand neural commonalities and differences underlying different emotion regulation strategies, the present study applied a meta-analytic method to fMRI studies examining task-related activity of reappraisal and acceptance. Results showed increased activity in left-inferior frontal gyrus and insula for both strategies, and decreased activity in the basal ganglia for reappraisal, as well as decreased activity in limbic regions for acceptance. These findings are discussed in the context of a model of common and specific neural mechanisms of emotion regulation that support and expand on the previous dual-routes models. We suggest that emotion regulation may rely on a core inhibitory circuit, as well as strategy-specific top-down and bottom-up processes that differ for each strategy.